BS EN 4882. Aerospace series. Steel X5CrNiCu 17-4 (1.4542). Air melted. Solution treated and precipitation treated. Sheets and strips. a ≤ 6 mm. Rm ≥ 1 070 MPa. (28th May 2021) - British Standards Institution,
No abstract available